The evaluation of a nucleoprotein ELISA for the detection of equine influenza antibodies and the differentiation of infected from vaccinated horses (DIVA). (December 2013) - Galvin, Pamela; Gildea, Sarah; Arkins, Sean; Walsh, Cathal; Cullinane, Ann
Abstract : Background: Antibodies against equine influenza virus (EIV) are traditionally quantified by haemagglutination inhibition (HI) or single radial haemolysis (SRH). Objectives: To evaluate an ELISA for the detection of antibodies against influenza nucleoprotein in the diagnosis and surveillance of equine influenza (EI). Methods: The ELISA was compared with the SRH and HI tests. Serial serum samples from 203 naturally and 14 experimentally infected horses, from 60 weanlings following primary vaccination with five different vaccines (two whole inactivated vaccines, two ISCOM‐based subunit vaccines and a recombinant canarypox virus vaccine) and from 44 adult horses following annual booster vaccination with six different vaccines were analysed. Results: Fewer seroconversions were detected in clinical samples by ELISA than by SRH or HI but ELISA was more sensitive than SRH in naïve foals post‐experimental infection. The ELISA did not detect the antibody response to vaccination with the recombinant canarypox virus vaccine confirming the usefulness of the combination of this kit and vaccine to differentiate between naturally infected and vaccinated horses, that is, DIVA. No DIVA capacity was evident with the other vaccines. Conclusion: The results suggest that this ELISA is a useful supplementary test for the diagnosis of EI although less sensitive than HI or SRH. It is an appropriate test for EI surveillance in a naïve population and may be combined with the recombinant canarypox virus vaccine but not with other commercially available subunit vaccines, in a DIVA strategy.